A study of the reality of digital transformation in the Syrian Ministry of FinanceA study of the reality of digital transformation in the Syrian Ministry of FinanceA study of the reality of digital transformation in the Syrian Ministry of FinanceA study o (Journal of Hama University, 2025)
Digital transformation through advanced technologies plays great importance, as it is exploited in public and private institutions, including the Ministry of Finance in the Syrian Arab Republic, which uses this technology to provide some of its services. The current study clarified the electronic services provided by the Ministry of Finance through an analysis of the electronic services provided and comparing them to non-automated services, in addition to studying the relationship between electronic services and the number of completed transactions.This study examined the reality of digital transformation in the Ministry of Finance through electronic services, which play a major role in influencing the number of completed transactions. The descriptive analytical approach was used, by studying the government data of the Ministry of Finance in Syria that serves the study, in order to reach the reality of using electronic services in the Ministry of Finance in Syria. These data were analyzed using the statistical program SPSS, and regression analysis was applied to find the relationship between dependent and independent variables.The most prominent results of this study are:- The number of electronic services provided by the Ministry of Finance in Syria affects the number of completed transactions. -There is a continuous increase in the number of automated transactions completed by the Ministry-The percentage of electronic services increased compared to non-automated services, and this is due to the Corona pandemic, which prompted auditors to use electronic services.
Keywords: Digital transformation, electronic services